Adsorption processes coupled with mass transport at macro-electrodes: New insights from simulation - Yang, M; Compton, RG (Elsevier, 2019)
A general simulation model is developed for voltammetry of species adsorbed from solution involving coupled mass transport and adsorption which distinguishes the relative contributions from the adsorption kinetics, the mass transport and electron transfer kinetics of the reactants and products. The model assumes only the adsorbed species are electrochemically active. To provide meaningful insights, we focus on three limiting cases in which the fate of the formed product differs. In Case One, the product remains on the surface and does not desorb; in Case Two, the product desorbs slowly into solution; in Case Three, the product desorbs rapidly into solution. In each case, the effect of independent parameters such as the adsorption rate constants, the electron transfer kinetics and the voltage scan rate are investigated. New insights from this simulation include a steady state voltage-current response for a macro-electrode when rate determining step becomes ‘bottlenecked’ by the slow desorption of the product. Furthermore, when the rate of adsorption and desorption of the reaction and product are fast compared to the mass transport and are not rate determining, the simulated current for the redox process via the adsorption pathway can be ca. 2.3 times higher to that when electron transfer occurs via the solution phase.